Climate change-driven shifts in the global distribution of tomato and potato crops and their associated bacterial pathogens - Hubab, Muhammad; Lorestani, Niloufar; Al-Awabdeh, Rogayah Akram Mheisin; Shabani, Farzin (Frontiers in Microbiology, 2025)
IntroductionClimate change is increasingly affecting the global distribution and productivity of critical food crops, including Solanum lycopersicum (tomato) and Solanum tuberosum (potato). In particular, bacterial pathogens such as Clavibacter michiganensis and Ralstonia solanacearum are expected to shift their geographic ranges, posing new risks to these crops. This study hypothesizes that under future climate scenarios, the geographic overlap between these crops and their pathogens will increase in certain regions, leading to heightened agricultural risks, especially in areas currently considered safe from these pathogens.MethodsTo test our hypotheses, the objective was to evaluate the potential impact of climate change on the geographic distribution of two key food crops (tomato and potato) and their bacterial pathogens for the current time and by 2050. This study used four species distribution models (SDMs) to predict current and future habitat suitability for both tomato and potato crops, as well as their associated pathogens, under two shared socioeconomic pathways (SSP4.5 and SSP8.5) and four global circulation models (GCMs).ResultsThe models projected significant poleward shifts in suitable habitats for tomatoes and potatoes, with notable expansions in higher-latitude regions such as Canada, northern Europe, and Russia, and contractions in current major production zones such as the United States (US), Brazil, parts of Africa, and China. For Clavibacter michiganensis, the overlap with tomatoes was substantial, whereas the overlap between potatoes and Ralstonia solanacearum was comparatively smaller.DiscussionOur hypothesis was partially supported by the results. While the overall overlap between crop and pathogen habitats remains limited, the risk areas for both pathogens are expected to expand under future climate conditions in regions such as eastern Australia, Japan, Spain, and France. These findings underscore the importance of region-specific agricultural planning and pathogen management strategies to mitigate the risks posed by climate change. Future efforts should focus on vulnerable areas to prevent significant economic losses and ensure food security.